2002
DOI: 10.2337/diacare.25.8.1451
|View full text |Cite
|
Sign up to set email alerts
|

Walking Strategy in Diabetic Patients With Peripheral Neuropathy

Abstract: OBJECTIVE -Diabetic neuropathic patients show a peculiar loading pattern of the foot, which led us to hypothesize that a substantial modification exists in their deambulatory strategy. The aim of the present study was to support this hypothesis by quantifying the changes of the loading patterns and by monitoring the excursion of center of pressure (COP) during gait. RESEARCH DESIGN AND METHODS-A total of 21 healthy volunteers (C) and 61 diabetic patients were evaluated: 27 diabetic subjects without neuropathy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
79
0
17

Year Published

2003
2003
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 108 publications
(103 citation statements)
references
References 23 publications
7
79
0
17
Order By: Relevance
“…The study and control groups did not differ in height indicating that height did not confound stride length findings. Our results are in agreement with previous reports in which shorter stride lengths were accompanied by a decrease in the forward excursion of the center of pressure [32] as well as reduced ankle moment and power [27,29]. Reduced plantar flexor moment and reduced power at push off have also been described in subjects with DM as an attempt to provide the major positive work at push-off using their hip flexors [26].…”
Section: Discussionsupporting
confidence: 93%
“…The study and control groups did not differ in height indicating that height did not confound stride length findings. Our results are in agreement with previous reports in which shorter stride lengths were accompanied by a decrease in the forward excursion of the center of pressure [32] as well as reduced ankle moment and power [27,29]. Reduced plantar flexor moment and reduced power at push off have also been described in subjects with DM as an attempt to provide the major positive work at push-off using their hip flexors [26].…”
Section: Discussionsupporting
confidence: 93%
“…1). The observed reduction of plantarflexion between the Sha-Cal during FFPOP in the PwDM_NP reflects a deviant third rocker and is probably related to the above mentioned 'cautious walking strategy' (Giacomozzi et al, 2002). Kerrigan et al (1998) observed a similar reduction in ankle plantarflexion in elderly subjects and inferred it as an adaptive strategy to maintain greater foot-to-floor contact during terminal stance.…”
Section: Discussionmentioning
confidence: 61%
“…A delayed heel off was detected in this group (P = 0.021). A more conservative walking strategy can be considered as a plausible explanation, as this is characterized by a less prominent propulsive phase (Giacomozzi et al, 2002). This assumption can be further underpinned by the fact that the FFPOP was significantly shorter in the PwDM_NP group (Additional file 1).…”
Section: Discussionmentioning
confidence: 99%
“…These structural and functional changes have been recognized as responsible for increased plantar pressures (7,20) . In a previous study, we observed that significant changes in forefoot GRF components may be present in diabetic patients without neuropathy (21), thus suggesting that other modifications, independent from peripheral neuropathy, may occur.…”
Section: Discussionmentioning
confidence: 99%